Growth trends of the adult hospitalist workforce between 2012 and 2019. Issue 11 (30th August 2022) - Lapps, Joshua; Flansbaum, Bradley; Leykum, Luci K.; Bischoff, Heidi; Howell, Eric
Abstract: Background: Accurately identifying the number of practicing hospitalists across the United States continues to be a challenge. Characterizing the workforce is important in the context of healthcare reforms and public reporting. Objective: We sought to estimate the number of adult hospitalists practicing in the United States over an 8‐year period, to examine patterns in growth, and begin to explore billing patterns. Design, Settings, and Participants: Retrospective study using national Medicare Part B claims datasets. We applied a commonly used 90% threshold of billing hospital visit‐associated Healthcare Common Procedure Coding System codes to identify adult hospitalists in publicly available Medicare Provider Utilization and Payment data for 2012–2019. We then analyzed billing patterns for those identified hospitalists. Main Outcomes and Measures: Identify trends in the number of identified adult hospitalists, including those self‐identified. Compare hospitalists' billing to that of non‐hospitalist Internal Medicine and Family Medicine physicians. Results: We saw more than a 50% growth rate of practicing adult hospitalists between 2012 and 2019. In 2019, we identified 44, 037 adult hospitalists. Conclusions: The number of adult hospitalists continued to grow at a consistent rate, such that hospitalists are in the top five largest physician specialties in the United States. In the absence of more formal identification and consistent use by hospitalists, a threshold continues to be a meaningful tool to characterize the workforce.